Key experiences of primary social groups in Unspecified Kidney Donation. Issue 3 (3rd June 2019) - Clarke, Alexis; Mitchell, Annie; Williams, Lynsey; Kirk, Adam; Auburn, Tim; Price, Linnie; Shorrock, Jan; Chester, Lucy
SUMMARY: Background: The role of family members in directed kidney donation is well documented in the literature from both a physiological and psychosocial perspective. The experiences of families, or primary social groups (PSGs), where one member considers donating a kidney via unspecified altruistic kidney donation route (UKD) is poorly understood. This is pertinent as lack of family support has been identified as a potential contributor to donation withdrawal. Objectives: This study aimed to explore the relevant psychosocial factors underpinning completed and uncompleted donations. Design: A qualitative study using semi–structured interviews. Participants: Qualitative interviews were conducted in the United Kingdom with 35 individuals comprising of: 11 donors who donated their kidney altruistically and 8 of their PSG members, and 11 donors who withdrew and 5 of their PSG members. Approach: Interviews were transcribed verbatim and analysed using Framework Analysis. Results: Two major themes were identified: (1) Supportability, which contained experiences fundamental to proceeding to donate, underpinned by four subthemes Acceptability, Awareness and Information, Family Risk and Ambivalence;(2) Seeking Resolution, contained discussions of experiences following either withdrawal from or completion of the donation, and comprised two sub–themes, Unfinished Business and Resolve. Conclusions: There are key differences in the experiences between those who completed their donation and those who withdrew. It is clear from this study that UKD operates within a PSG's social framework. Clinical implications suggest interventions at the level of addressing ambivalence within the PSG and the need for promotion of better psychosocial outcomes both following completion or withdrawal from donation.